2018
DOI: 10.1007/s11998-018-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and properties of graphene oxide/urushiol-formaldehyde polymer composite coating

Abstract: Graphene oxide (GO) was modified by 3methacryloxypropyltrimethoxysilane (MPS) to obtain modified graphene oxide (MGO). MGO was dispersed in urushiol-formaldehyde polymer by mechanical mixing and ultrasonic dispersion, and MGO/urushiolformaldehyde polymer (UFP) coatings with different MGO contents were fabricated. The microstructure, physico-mechanical properties, and electrochemical properties of the MGO/UFP composite coatings were investigated. The results indicated that the hardness, adhesion, and corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The total mass loss of GO (Figure 4b) is obviously higher than that of piperazine-GO (Figure 4a), especially the second mass loss, which demonstrates the higher thermal stability of piperazine-GO owing to the logical decrease in the amount of oxygen-containing functional groups in the modified GO. [75][76][77] The final mass loss in the TGA curve of piperazine-GO (Figure 4a) is caused by the decomposition of organic parts located on its surface. The morphological properties of piperazine-GO were examined by means of TEM and FE-SEM.…”
Section: Results and Discussion Synthesis And Characterization Of Piperazine-gomentioning
confidence: 99%
“…The total mass loss of GO (Figure 4b) is obviously higher than that of piperazine-GO (Figure 4a), especially the second mass loss, which demonstrates the higher thermal stability of piperazine-GO owing to the logical decrease in the amount of oxygen-containing functional groups in the modified GO. [75][76][77] The final mass loss in the TGA curve of piperazine-GO (Figure 4a) is caused by the decomposition of organic parts located on its surface. The morphological properties of piperazine-GO were examined by means of TEM and FE-SEM.…”
Section: Results and Discussion Synthesis And Characterization Of Piperazine-gomentioning
confidence: 99%
“…[58,59] By mechanical mixing and ultrasonic dispersion, modified graphene oxide (MGO) was dispersed in urushiol formaldehyde polymer (UFP) by Zhang et al, and modified graphene oxide/urushiol formaldehyde polymer (MGO/UFP) coatings with different MGO content were prepared. [51,60] It is found that GO connected with the modifier 3methacryloxypropyltrimethoxysilane (MPS) through chemical bond, and the chemical grafting of MPS molecules onto the surface of GO enhanced the dispersion and compatibility of the GO with UFP. [60] Thus the MGO/UFP composite coating derived from the reaction between MGO and UFP could perform as a major anti-corrosion coating, which provided a more effective barrier against corrosive ions ingress.…”
Section: Nano-materials Modificationmentioning
confidence: 99%
“…Graphene–poly(4-vinylpyridine-co-butyl methacrylate) enhances the corrosion resistance of copper by electrophoretic deposition [ 203 ]. The anticorrosion properties are enhanced using GO-3-methacryloxypropyltrimethoxysilane/urushiol-formaldehyde polymer coatings [ 204 ].…”
Section: Applicationsmentioning
confidence: 99%